Make Me Want to Pay. A Three-Way Interaction Between Procedural Justice, Distributive Justice, and Power on Voluntary Tax Compliance - van Dijke, Marius; Gobena, Lemessa Bayissa; Verboon, Peter (Frontiers in Psychology, 2019)
Tax compliance involves a decision where personal benefits come at the expense of society and its members. We explored the roles of procedural and distributive justice and citizens’ perceptions of the tax authority’s power in stimulating voluntary tax compliance. Distributive and procedural justice have often (but not always) been shown to interact in such a way that high distributive justice or high procedural justice is sufficient to predict positive responses to authorities and the social collective they represent. We examined whether this interaction predicts voluntary (but not enforced) tax compliance, in particular among citizens who perceive the tax authority’s power as high (vs. low). The results of two field studies among Ethiopian (Study 1) and US (Study 2) taxpayers supported our predictions. With this research we connect the roles of two core social psychological antecedents of tax compliance (i.e., distributive and procedural justice) with that of a deterrent factor (i.e., authority power) and obtain support for the psychological process underlying the Distributive Justice × Procedural Justice interaction in two diverging tax environments.